Automatic processing of emotional facial expressions as a function of social anhedonia. (30th December 2017) - Günther, Vivien; Zimmer, Juliane; Kersting, Anette; Hoffmann, Karl-Titus; Lobsien, Donald; Suslow, Thomas
Abstract: Anhedonia is an important feature of major depression and schizophrenia-spectrum disorders. Few neuroimaging studies have investigated neural alterations in high anhedonia, isolated from other psychopathological variables, by including only participants without clinical diagnoses. The present study examined healthy individuals scoring high ( N = 18) vs. low ( N = 19) in social anhedonia, who were carefully selected from a sample of N = 282 participants. To examine differences in automatic brain responses to social-affective stimuli between high vs. low social anhedonia participants, we used functional magnetic resonance imaging. To assess early, automatic stages of emotion processing, we administered a paradigm presenting brief (33 ms), backward-masked happy, sad, and neutral facial expressions. Individuals high in social anhedonia demonstrated increased activation in the bilateral thalamus and left red nucleus in response to masked sad faces relative to individuals low in social anhedonia. No significant group differences in brain activation emerged in other regions known to be involved in emotion and reward processing, including the amygdala and nucleus accumbens. Our results suggest that high social anhedonia in otherwise healthy individuals is associated with exaggerated automatic reactivity in the thalamus, which is a brain structure that has been implicated in the mediation of attentional processes. Highlights: Individuals scoring high vs. low in social anhedonia were examined. Participants were recruited from a sample of N = 282 healthy volunteers. Automatic brain responses to emotional facial expressions were investigated. In high social anhedonia an increased thalamic responsivity to sad faces was observed.